(untitled) (Third Sector Social Economic Review, 2017)
The cooperative movement, which started with the Pre-Republican Country Funds in our country, was able to develop with some steps taken after the republic. However, even though the basic socio-cultural values of the Turkish society have helping, imece and Ahilik-like constructions and understandings, cooperatives has not shown sufficient and desired development in Turkey. When this problem is examined, it will be revealed that there are problems related to each other, which are mainly based on legal, economic, educational and other problems. It is very important that these problems are solved by a holistic approach on the axis of cooperatives in Turkey.